Risk factors and outcome of pulmonary aspergillosis in critically ill coronavirus disease 2019 patients—a multinational observational study by the European Confederation of Medical Mycology. (April 2022) - Prattes, Juergen; Wauters, Joost; Giacobbe, Daniele Roberto; Salmanton-García, Jon; Maertens, Johan; Bourgeois, Marc; Reynders, Marijke; Rutsaert, Lynn; Van Regenmortel, Niels; Lormans, Piet; Feys, Simon; Reisinger, Alexander Christian; et al.
Abstract: Objectives: Coronavirus disease 2019 (COVID-19) -associated pulmonary aspergillosis (CAPA) has emerged as a complication in critically ill COVID-19 patients. The objectives of this multinational study were to determine the prevalence of CAPA in patients with COVID-19 in intensive care units (ICU) and to investigate risk factors for CAPA as well as outcome. Methods: The European Confederation of Medical Mycology (ECMM) conducted a multinational study including 20 centres from nine countries to assess epidemiology, risk factors and outcome of CAPA. CAPA was defined according to the 2020 ECMM/ISHAM consensus definitions. Results: A total of 592 patients were included in this study, including 11 (1.9%) patients with histologically proven CAPA, 80 (13.5%) with probable CAPA, 18 (3%) with possible CAPA and 483 (81.6%) without CAPA. CAPA was diagnosed a median of 8 days (range 0–31 days) after ICU admission predominantly in older patients (adjusted hazard ratio (aHR) 1.04 per year; 95% CI 1.02–1.06) with any form of invasive respiratory support (HR 3.4; 95% CI 1.84–6.25) and receiving tocilizumab (HR 2.45; 95% CI 1.41–4.25). Median prevalence of CAPA per centre was 10.7% (range 1.7%–26.8%). CAPA was associated with significantly lower 90-day ICU survival rate (29% in patients with CAPA versus 57% in patients without CAPA; Mantel–Byar p < 0.001) and remained an independent negative prognostic variable after adjusting for other predictors of survival (HR 2.14; 95% CI 1.59–2.87, p ≤ 0.001). Conclusion: Prevalence of CAPA varied between centres. CAPA was significantly more prevalent among older patients, patients receiving invasive ventilation and patients receiving tocilizumab, and was an independent strong predictor of ICU mortality.